Zmanjšana stopnja razplinjevanja elektrokemijsko zlatenih srebrnih kontaktnih površin v hermetičnih relejih - Koller, Lidija (Kovine zlitine tehnologije, 1995)
The surface gold electroplated layer appears an important role for hermetic relays, simultaneously decreasing contact resistance and increasing their lifetime. Silver alloy (Ag with 0,1 wt. % Mg) is gold electroplated, the thickness of gold layer is approximately ?$0,5μ$?. Annealing at 135°C and 200°C provide a surface of extremely low autgassing at contact operation. The surface gold layer is investigated by means of Auger Electron Spectroscopy and the outgassed products by means of mass spectroscopy in the experimental system which was developed and build for this purpose at the Institute for Electronics and Vacuum Technique. Gold electroplating and subsequent annealing improve the desorption of surface and produce relatively dry surface low outgassing state.
Keywords: kontaktni materiali; površine; razplinjevanje; hermetični releji